2016
DOI: 10.3390/atmos7030043
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing Fire Records from Ground-Based Routine Aerosol Monitoring

Abstract: Long-term fire records are important to understanding the trend of biomass burning and its interactions with air quality and climate at regional and global scales. Traditionally, such data have been compiled from ground surveys or satellite remote sensing. To obtain aerosol information during a fire event to use in analyzing air quality, we propose a new method of developing a long-term fire record for the contiguous United States using an unconventional data source: ground-based aerosol monitoring. Assisted b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Some fraction indicators were selected for assessing the relationship between biomass burning and regional haze. In general, high PM 2.5 /PM 10 , OC/EC, and K/EC ratios were indices for biomass burning [9,24]. High ratios of PM 10 /SO 2 and CO/SO 2 showed that air quality was heavily impacted by wheat straw burning, and these ratios can be employed as indicators of the contribution of wheat straw burning to the degradation of Beijing air quality [37].…”
Section: Relationship Between Biomass Burning and Regional Hazementioning
confidence: 98%
See 1 more Smart Citation
“…Some fraction indicators were selected for assessing the relationship between biomass burning and regional haze. In general, high PM 2.5 /PM 10 , OC/EC, and K/EC ratios were indices for biomass burning [9,24]. High ratios of PM 10 /SO 2 and CO/SO 2 showed that air quality was heavily impacted by wheat straw burning, and these ratios can be employed as indicators of the contribution of wheat straw burning to the degradation of Beijing air quality [37].…”
Section: Relationship Between Biomass Burning and Regional Hazementioning
confidence: 98%
“…Emissions from biomass burning are known as a source of greenhouse gases such as carbon dioxide, methane, and nitrous oxide. Furthermore, aerosols emitted from biomass burning have high mass concentrations of PM 2.5 (particles smaller than 2.5 µm in diameters), OC (organic carbon), EC (elemental carbon) and K (potassium) [24]. Reports suggest that approximately 50-70% of the mass of all particle emissions from biomass burning is carbon, with OC and EC accounting for 55% and 8% of fine particle mass, respectively [25].…”
Section: Agricultural Open Field Biomass Burning In Chinamentioning
confidence: 99%